The factors of students’ acceptance on Open and Distance Learning (ODL) in UiTM Seremban 3 / Nur Anis Zakirah Mohd Nor and Fatin Izniey Syazwaniey Mohd Fauzi - Mohd Nor, Nur Anis Zakirah; Mohd Fauzi, Fatin Izniey Syazwaniey (2022)
The purpose of the study was to examine the factors of students’ acceptance on Open and Distance Learning (ODL) implementation in UiTM Seremban 3. Before this, the introduction of online learning or e-learning is usually implemented in developed country and this situation have changes drastically especially after the pandemic of Covid-19. In 2020, Malaysia is one of the countries that faced the outbreak of Covid-19 which was started from Wuhan, China and this virus does not only affect our economy, but also to our educational process and institutions. Apart from that, our government through Ministry of Education took an initiative by implementing the Open and Distance Learning (ODL) in ensuring the continuation of educational process for the students in Malaysia. Therefore, to answer the research questions and research objectives, a quantitative method has been applied in this study. This study managed to gather information from a total of 303 respondents that were selected based on convenience sampling technique. In this study, the results discovered that there were four factors of students’ acceptance on Open and Distance Learning (ODL) implementation in UiTM Seremban 3, specifically social norms, mental health, technology and student’s attitude. The inputs of this study found that that there are significant relationships between all of the independent variables toward the student’s acceptance of Open and Distance Learning (ODL) implementation in UiTM Seremban 3. A detailed discussion of the research is extended in this study.